2021
DOI: 10.3390/ijerph18041735
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Mental Health, and Well-Being in Very Pre-Term and Term Born Adolescents: An Individual Participant Data Meta-Analysis of Two Accelerometry Studies

Abstract: This study examined whether physical activity is associated with better mental health and well-being among very preterm (≤32 weeks) and term born (≥37 weeks) adolescents alike or whether the associations are stronger in either of the groups. Physical activity was measured with accelerometry in children born very preterm and at term in two cohorts, the Basel Study of Preterm Children (BSPC; 40 adolescents born ≤32 weeks of gestation and 59 term born controls aged 12.3 years) and the Millennium Cohort Study (MCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
1
11
3
Order By: Relevance
“…On average, VP/VLBW individuals have more motor problems which often persist into adulthood [53][54][55]67 and may thus participate less in physical activity, 68 further relating to more peer problems. 69,70 Furthermore, cognitive ability might be more influential on social competence than is physical ability. 47 Harrison suggested that VLBW children have cognitive and behavioural deficits that isolate them from both their peers and their peers' risk-taking behaviour in the absence of NSI.…”
Section: Discussionmentioning
confidence: 99%
“…On average, VP/VLBW individuals have more motor problems which often persist into adulthood [53][54][55]67 and may thus participate less in physical activity, 68 further relating to more peer problems. 69,70 Furthermore, cognitive ability might be more influential on social competence than is physical ability. 47 Harrison suggested that VLBW children have cognitive and behavioural deficits that isolate them from both their peers and their peers' risk-taking behaviour in the absence of NSI.…”
Section: Discussionmentioning
confidence: 99%
“…Many preterm-born young adults attain lower education [56,57] and are less likely than their term-born counterparts to have couple relationships, start a family and have children [58]. There is also evidence that preterm birth is associated with certain lifestyle factors, including sedentary behaviour [59,60]. Multimorbidity could mediate the association of preterm birth with educational achievement or physical activity, or low socioeconomic position, living alone or sedentary lifestyle could be risk factors for multimorbidity among individuals with a preterm-born background.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In a physical and psychological sense, adolescence marks a sensitive growth phase [ 1 ], which starts during puberty and finishes with bio-psychosocial maturity [ 2 ]. It typically takes place between 10 and 19 years of age [ 3 ].…”
Section: Introductionmentioning
confidence: 99%